Deinococcus rufus sp. nov., isolated from soil near an iron factory - Wang, Qian; Song, Yali; Choi, Lina; Liu, Hongyu; Wang, Gejiao; Li, Mingshun (International journal of systematic and evolutionary microbiology, 2018)
A Gram-stain-negative, non-motile, rod-shaped, red-pigmented strain, designated W37 , was isolated from soil near an iron factory in Busan (Republic of Korea). Phylogenetic analysis based on 16S rRNA gene sequences showed that strain W37 was most closely related to Deinococcus yunweiensis YIM 007 (98.3 %) and Deinococcus radioresistens 8A (96.3 %). The DNA-DNA relatedness between strain W37 and D. yunweiensis YIM 007 was 50.5 %. The predominant respiratory quinone was MK-8. The major polar lipids were an unidentified phosphoglycolipid, an unidentified aminophospholipid, four unidentified glycolipids, two unidentified phospholipids and an unidentified lipid. The major fatty acids (>5 %) of strain W37 were summed feature 3 (C16 : 1ω7c and/or iso-C15 : 0 2-OH), C16 : 0, C17 : 1ω8c and iso-C17 : 1ω9c. The DNA G+C content was 69.0 mol%. Moreover, the chemo-physical characteristics of strain W37 clearly differed from those of related species, including ranges of growth temperature and pH, positive activity for 4-hydroxybenzoate and negative activity for cystine arylamidase. Phenotypic, chemotaxonomic and genotypic analyses indicated that strain W37 represents a novel species of the genus Deinococcus, for which the name Deinococcus rufus sp. nov., is proposed. The type strain is W37 (=KCTC 33913 =CCTCC AB 2017081 ).